Influence Of The Noise Intensity And Compliance Using Early Equipment On Blood Pressure On Workers In PT. Pindad Turen - Dewi Nurandika, Yunda; Sari, Nia; Dian Ellina, Agusta (Journal of Global Research in Public Health, 2019)
Each job has a potential hazard that can cause work accidents or diseases, one of which is the noise hazard that can cause an increase in blood pressure. To reduce the danger of noise induced, the workers can be using APT like earplug and earmuff. But in the preliminary study at PT. Pindad (Persero) noise generated by one machine reaches 98 dB (A) and almost the majority of workers don’t use APT. This research want to knowing influence of the noise intensity and compliance using early equipment (apt) on blood pressure on workers In pt. Pindad (persero) turen. The research design used analytic observational research using cross-sectional approach. Technique to determine the sample using non random method (non probability) sampling that is using purposive sampling technique. Its population is employees of PT. Pindad (Persero) with respondents of 30 respondents in the tooling. The result of this research is Signification value of noise variable to systole = 0,036 and 0,024 to blood pressure of diastole. Since the Sig is both <α (0.05) then there is an effect of noise intensity on blood pressure. While Signification the value of compliance variable to systole=0.714 and 0.370 for diastolic blood pressure. So it can be concluded that there is no relationship between adherence APT use with increased blood pressure. The compliance didn”t influence this blood pressure because the compliance using APT is no reduce the risk are negative from exposure to noise. While the exposure to noise high intensity led to an increase hormone cortisol so that led to increases in the blood pressure on workers after them work. To decrease it, beside the workers are obliged to use APD, better there there are strict sanctions fork the workers who don’t use APD